Introduction to a new array processing concept : orientational beamforming - Aye, Su Yee (2021)
The article explains the orientational beamforming concept from a perspective of spread-spectrum communication not in the frequency domain but in the spatial domain. In the orientational beamforming concept, radiated signal energy is spread over a certain part of or the entire angular range by a transmit array with randomly (practically pseudo-random) distributed antennas. At the receiving end, an identical pseudo-random array is employed so that the matching of the antenna distributions between the transmit and receive arrays spatially collects and recovers the signal of interest. An orientational alignment of identical arrays is exploited to perform the beamforming. We have observed that the newly discovered spatial domain can eliminate the necessity of knowing the signal direction to obtain beamforming. Consequently, the matched array processing system improves the interference suppression capability, especially when directional interfering signals exist. The concept is also applicable to the near-field scenario without being affected by spherical wavefront delays in forming an array beam. In this article, proposed orientational beamforming in combination with conventional directional beamforming is also discussed.